Targeting Grenada’s most deprived population: a multidimensional living conditions assessment - Diaz, Y; Espinoza, F; Markaki, Y; Sanchez-Cespedes, L (Oxford Poverty & Human Development Initiative (OPHI), 2015)
Public policies concerned with the reduction of poverty increasingly rely on identifying the most deprived households with the use of statistical targeting techniques. Targeting methods aim to measure deprivation as accurately as possible and use this measurement to identify those who need help the most. This paper proposes an improved method for the construction of a household multidimensional index of deprivation for targeting purposes and applies it in the Grenadian context. The proposed Grenadian living conditions index prioritizes quality of life and living conditions, rather than merely income or expenditure and provides a framework for the measurement of the joint depth of multidimensional deprivation. Furthermore, the proposed instrument allows for comparisons across households and over time and can be applied for different purposes and policies. Empirical results shed light on the advantages of using our proposed method for poverty reduction, compared to Principal Component Analysis and Fuzzy Set techniques.